The wellbeing of families: Conceptual issues and unique insights from Growing up in Australia - Hayes, A; Gray, M; Baxter, Jennifer (My University, 2007)
The Longitudinal Study of Australian Children provides a window to the wellbeing of families. The measurement and definition of family wellbeing is explored in this presentation. The presentation gives an overview of the study and what it tells us about wellbeing. It includes data on many aspects of wellbeing.
Keywords: Health; Health -- Wellbeing; Families; Health and wellbeing; Families and relationships; Families; Health; Wellbeing; Health and wellbeing; Families and relationships